As varas empresariais no ordenamento jurídico brasileiro - Guinsani, Felipe (2024)
This dissertation explores the evolution and current state of specialized business courts in the Brazilian judicial system, emphasizing their role in enhancing legal certainty, efficiency, and quality in decision-making. The study investigates the concept of specialization, its historical implementation, and contemporary challenges, including procedural viscosity, the selection process of judges, and jurisdictional deterritorialization. It includes a comprehensive statistical analysis of the distribution of cases, the number of established courts, congestion rates, and the volume of cases judged. Additionally, the dissertation outlines the introduction and expansion of business courts in various Brazilian states, including São Paulo, Rio de Janeiro, Minas Gerais, Rio Grande do Sul, Bahia, and Ceará, detailing the legislative resolutions and changes that facilitated these developments. It also discusses the integration of technological advancements, such as the Electronic Judicial Process and the Justice 4.0 Program, which contribute to the modernization of the judiciary and expanded access to justice. Ultimately, the dissertation evaluates the positive outcomes and ongoing challenges of specialization, highlighting the constant need for adaptation and improvement of the judicial system to effectively meet the complex demands of contemporary business law.